Gottland Mariusza Szczygła w czeskim przekładzie i jego czeska recepcja - Mroczek, Izabela (Przekłady Literatur Słowiańskich, 2011)
Czech translation of Mariusz Szczygieł’s Gottland and its Czech reception Mariusz Szczygieł’s Gottland presents Czech modern history by descripting “private stories” of people, that are unknown or slightly known in Poland. Among them we can find: Tomáš Bat’a, Lída Baarová, Otakar Švec, Karel Fabián, Marta Kubišová and Evald Schorm. Czech critiques underline, that this book shows the character of Czech nation, is a mirror of Czech complexes and traumas. An enormous popularity of Gottland in Czech Republic proves, that Czechs still need publications, which could help with describing their modern identity and their position among European nations. Despite of its popularity, we can find many differences between original text and its Czech translation made by Helena Stachová: not only in dates and names, but also in citations and dialogues introduced to Polish book in Mariusz Szczygieł’s translation from Czech language.